Analysis of 3A Theory in Making Coban Pelangi Waterfall A Natural Tourism Attraction in Gubugklakah - Audrey, Kent; Kevin; Manjou Odira; Budi Setiawan (Indonesian Journal Publisher, 2025)
This study examines the implementation of the 3A theory (Attractions, Accessibility, and Amenities) in the development of Coban Pelangi Waterfall as a natural tourism attraction in Gubugklakah, East Java, Indonesia. The waterfall’s natural beauty, highlighted by its unique rainbow phenomenon, is the primary attraction, drawing both domestic and international visitors. Accessibility is assessed based on transportation networks, road conditions, infrastructure quality, and the ease of navigation within the site, which play critical roles in enhancing the overall visitor experience. The analysis of amenities focuses on essential facilities like parking areas, public restrooms, and accommodation options, as well as additional features such as food stalls and souvenir shops that contribute to visitor satisfaction. Using qualitative research methods, including field observations and interviews with visitors, the study identifies strengths such as the site’s captivating natural appeal, serene environment, and existing recreational activities, including trekking and photography. However, challenges remain in improving infrastructure, such as better road conditions, enhanced waste management systems, and the availability of clear directional signs to facilitate smoother navigation. The findings underscore the importance of strategic enhancements in these areas to boost visitor satisfaction, ensure environmental sustainability, and promote Coban Pelangi as a competitive and well-rounded tourism destination. Furthermore, the study highlights the potential benefits of involving local communities in conservation efforts and tourism management, fostering a sense of ownership and economic opportunity.